The In Vitro Antibacterial Activity of Argirium SUNc against Most Common Pathogenic and Spoilage Food Bacteria - Andrea Mancusi; Marica Egidio; Raffaele Marrone; Luca Scotti; Domenico Paludi; Irene Dini; Yolande Thérèse Rose Proroga (MDPI AG, 2024)
Foodborne diseases are one of the main issues for human health, and antibacterial packaging plays a major role in food security assurance. Silver ultra nanoparticles (Argirium SUNc) are antimicrobial agents that have a wide spectrum of action, including against pathogenic bacteria and spoilage fungi. The aim of the present study was to evaluate the antibacterial activity of Argirium SUNc on the bacteria most commonly found in food: Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Listeria monocytogenes, and Salmonella typhimurium. In this regard, an in vitro study was carried out by assessing the Argirium SUNc effectiveness on different concentrations of each tested microbial strain and at different time intervals. The data showed that the antimicrobial activity of Argirium SUNc was directly related to the microbial concentration and varied depending on the microbial species. Moreover, a greater effectiveness against Gram-negative bacteria than Gram-positive bacteria was observed. These preliminary results provided important information on the silver nanoparticles spectrum of action, and this is an aspect that appears particularly promising for obtaining a viable alternative to traditional antimicrobials to be used against the pathogens and spoilage agents most commonly found in the food chain, harmful both to health and quality aspects.